Host DNA released by NETosis in neutrophils exposed to seasonal H1N1 and highly pathogenic H5N1 influenza viruses - Chan, Louisa L. Y. (2021)
Background: Neutrophil is of the most abundant number in human immune system. During acute influenza virus infection, neutrophils are already active in the early phase of inflammation - a time in which clinical biopsy or autopsy material is not readily available. However, the role of neutrophil in virus infection is not well understood. Here, we studied the role of neutrophil in host defense during influenza A virus infection, specifically assessing if it contributes to the differential pathogenesis in H5N1 disease. Methods: Neutrophils were freshly isolated from healthy volunteers and subjected to direct influenza H1N1 and H5N1 virus infection in vitro. The ability of the naïve neutrophils to infiltrate from the basolateral to the apical phase of the influenza virus infected alveolar epithelium was assessed. The viral replication, innate immune responses and Neutrophil extracellular trap (NET) formation of neutrophils upon influenza virus infection were evaluated. Results: Our results demonstrated that influenza virus infected alveolar epithelium allowed neutrophil transmigration. Significantly more neutrophils migrated across the H5N1 influenza virus infected the epithelium than the counterpart infected by the seasonal influenza H1N1 virus infected. Neutrophils were equally susceptible to H5N1 and H1N1 virus infection with similar viral gene transcription. Productive replication was observed in H5N1 infected neutrophils. H5N1 induced higher cytokine and chemokine gene transcription than H1N1 infected neutrophils, including TNF-α, IFN-β, CXCL10, MIP-1α and IL-8. This inferred a more intense inflammatory response posed by H5N1 than H1N1 virus. Strikingly, NADPH oxidase-independent NET formation was only observed in H1N1 infected neutrophils at 6 hpi while no NET formation was observed upon H5N1 infection. Conclusion: Our data is the first to demonstrate that NET formation is abrogated in H5N1 influenza virus infection and might contribute to the severity of H5N1 disease.